How Natural is the Natural Rate of Unemployment? - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2014)
The natural in the natural rate of unemployment is a misnomer, insofar as unemployment does not occur in nature. The concept is especially misleading because many economists and media commentators inappropriately equate it with full employment. As a consequence, endemic un- and underemployment is accepted as an inevitable attribute of the labor market. This is inaccurate inasmuch as the concept assumes that the institutional structure of the labor market is held constant. However, with creative restructuring of that market our aim should be bring the underemployment rate down to 1.2%, the rate that obtained in 1944 and which probably represents the lower bound rate physically attainable. Instead of the prevailing system, the right to work needs to be recognized as a natural right, because the right to life depends upon it. Several ways are proposed to create an inclusive labor market that distributes the available work in a more equitable fashion than the current system.
Keywords: J48; 330; natural rate of unemployment; labor market; underemployment; right to work; work sharing